Karakteristik Fisiokimia Minuman Serbuk Siwalan Berbahan Dasar Buah Siwalan dan Buah Nanas - Syarifa Ramadhani Nurbaya; M. Arief Setya Budi; Rima Azara; Lukman Hadi (Program Studi Teknologi Hasil Pertanian, 2026)
The objective of this study was to determine the characteristics of siwalan powder beverages made from siwalan fruit (Borassus flabellifer L.) and pineapple (Ananas comosus). This study employed a factorial design with two factors. The first factor was proportion of siwalan and pineapple juice (90:10, 70:30, 50:50), while the second factor was the concentration of egg white powder (5%, 10%, 15%). The experiment was repeated three times. The best treatment was the siwalan powder drink (used foam mat drying method) with a siwalan-to-pineapple ratio of 90% : 10% and an egg white powder concentration of 10%, which had the following characteristics: moisture content 7.77%, vitamin C 0.05%, antioxidant activity 170.64 ppm (weak), solubility 43.26%, yield 18.01%, L* value of 81.57, a+ value of 4.84, and b+ value of 15.01. Siwalan powder drink can be one of the instant powdered beverages made from natural ingredients that are beneficial to health